2006
DOI: 10.1103/physreva.73.023616
|View full text |Cite
|
Sign up to set email alerts
|

Condensation temperature of interacting Bose gases with and without disorder

Abstract: The momentum-shell renormalization group ͑RG͒ is used to study the condensation of interacting Bose gases without and with disorder. First of all, for the homogeneous disorder-free Bose gas the interactioninduced shifts in the critical temperature and chemical potential are determined up to second order in the scattering length. The approach does not make use of dimensional reduction and is thus independent of previous derivations. Secondly, the RG is used together with the replica method to study the interact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 44 publications
1
81
0
Order By: Relevance
“…(1) K is the strength of the disorder: the disorder potential u( r) has averages u( r) = 0 and u( r, r ′ ) = Kδ( r − r ′ ) (the bar denotes the average all disorder configurations). The result (1) has been confirmed in [33] by one-loop Wilson renormalization-group calculations. The shift of the critical temperature for the continuous Bose gas has been also recently computed in [35] using the Popov method, obtaining a value for the relative shift δT c /T (0) c which differs by a factor of 1/2 from the result (1).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…(1) K is the strength of the disorder: the disorder potential u( r) has averages u( r) = 0 and u( r, r ′ ) = Kδ( r − r ′ ) (the bar denotes the average all disorder configurations). The result (1) has been confirmed in [33] by one-loop Wilson renormalization-group calculations. The shift of the critical temperature for the continuous Bose gas has been also recently computed in [35] using the Popov method, obtaining a value for the relative shift δT c /T (0) c which differs by a factor of 1/2 from the result (1).…”
Section: Introductionsupporting
confidence: 68%
“…In presence of random on-site energies, T c increases for large filling, but much less than for for bond-disordered lattices, resulting in very small shift of T c for small disorder. These results should be compared with the findings for a continuous (i.e., without optical lattice) Bose gas in presence of a disordering potential [32,33,34,35,36]: without any confining potential, it has been shown that the critical temperature decreases with disorder [32]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…At asymptotically small ν → 0, numerical estimates give the shift of the critical temperature δT c ∼ −2ν/9π, which is close to the shift found in Refs. [24,25].…”
Section: White Noisementioning
confidence: 99%
“…Their results were recovered by Giorgini et al [23] using the hydrodynamic approximation, which is mathematically equivalent to the Bogolubov approximation. Lopatin and Vinokur [24] estimated the shift of the critical temperature due to weak disorder in a weakly interacting gas, which also was studied by Zobay [25], using renormalization group techniques. If the results obtained for asymptotically weak disorder are formally extended to strong disorder, then one comes [22,26] to the state, where n 0 = 0 but n s = 0, which corresponds to the Bose glass phase.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, such random potentials are realized by means of optical speckles [14][15][16][17]. Physical properties of these Bose systems in an external random potential have been theoretically studied for the case of weak disorder [18][19][20][21] and for arbitrarily strong disorder [22,23].…”
Section: Introductionmentioning
confidence: 99%